2006
DOI: 10.1186/1742-4690-3-63
|View full text |Cite
|
Sign up to set email alerts
|

Zidovudine plus lamivudine in Human T-Lymphotropic Virus type-I-associated myelopathy: a randomised trial

Abstract: Background: No therapies have been proven to persistently improve the outcome of HTLV-Iassociated myelopathy. Clinical benefit has been reported with zidovudine and with lamivudine in observational studies. We therefore conducted a randomised, double blind, placebo controlled study of six months combination therapy with these nucleoside analogues in sixteen patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
0
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(64 citation statements)
references
References 29 publications
3
56
0
5
Order By: Relevance
“…Reports have showed the limited value of corticosteroids, interferon-alpha and interferon-beta1a [63][64][65]. The combination of two nucleoside analogs (zidovudine and lamivudine) has been evaluated in a randomized, double-blind, placebo-controlled study with 16 HAM/TSP patients and no clinical improvement was observed [66]. Such treatment could be more effective in the early phases of the disease [60].…”
Section: Treatmentmentioning
confidence: 99%
“…Reports have showed the limited value of corticosteroids, interferon-alpha and interferon-beta1a [63][64][65]. The combination of two nucleoside analogs (zidovudine and lamivudine) has been evaluated in a randomized, double-blind, placebo-controlled study with 16 HAM/TSP patients and no clinical improvement was observed [66]. Such treatment could be more effective in the early phases of the disease [60].…”
Section: Treatmentmentioning
confidence: 99%
“…However, clinical studies showed no improvement in outcomes even when combination (AZT + 3TC) nucleoside reverse-transcriptase inhibitor therapy was used. 24 In contrast to these findings, a more recently published case of donor-derived HTLV-I infection and HAM/TSP in a renal transplant recipient, who was treated with the same antiretroviral combination (AZT + 3TC) and tapering course of steroids, reports some clinical improvement after 3 months of therapy. Long-term data on this patient are, however, lacking.…”
Section: Discussionmentioning
confidence: 91%
“…From the point of view of antiretroviral therapy, several studies have evaluated the role of zidovudine, lamivudine (in patients with or without myelopathy) [111] and raltegravir, with dissimilar and generally poor results. This is not surprising considering the higher levels of viral reproduction by division of infected cells than by intracellular viral replication.…”
Section: Treatmentmentioning
confidence: 99%